The impact of shareholder primacy on wage negotiations in the South African platinum mining industry. - Mthethwa, Themba Phillip (My University, 2016)
The purpose of this research was to critically assess, in the aftermath of the crippling five-month long platinum strike in 2014, the implications of the doctrine of shareholder primacy/sovereignty on corporate decision making in the platinum mining sector with specific reference to negotiations between mining companies and their employees on issues affecting the interests of non-shareholders such as employees. The research endeavoured to ascertain whether or not the corporate governance landscape in South Africa requires platinum mining companies to give life to the objectives of the Mineral and Petroleum Resources Development Act, 2002 (MPRDA), the Constitution of the republic of South Africa, 1996 (the Constitution) and the Companies Act, 71 of 2008 by extending its corporate social responsibility obligations beyond the threshold of enlightened shareholder value to make real contributions to society and the economy. The research also explored the extent to which long-term optimal profitability of the platinum mining industry is dependent on mining companies’ commitment to the restructuring of the shareholder sovereignty and primacy model to address weaknesses in the collective bargaining process and inequalities affecting the interests of all of its non-shareholding constituencies. Data was collected by sending questionnaires to the four biggest platinum mining houses, as well as organised labour to complete. The collected data were compared to 3 information published in these companies’ annual and other reports to obtain a corporate point of view on the issues under consideration. Most respondents were of the view that the legal policy of shareholder primacy that provides management of the platinum mines in South Africa, with its authority to decide upon salaries, should not be changed, or adapted to address the humane needs of miners. Mining houses are committed to various initiatives in terms of their Corporate Social Responsibility projects as regulated by the Mining Charter and Social and Labour Plans. Respondents are generally of the view that a change in the reliance on the doctrine of shareholder primacy is not likely to assure stakeholders in the mining industry that the driving forces behind the escalation of conflict and of deep-rooted conflict will be reduced or eradicated. The reason for this view is that there are several factors that contribute to the conflict within the Platinum mining industry. Most respondents were of the view that there is a need for a change in the wage negotiation agenda to address deep-rooted conflict and to engender trust in the relationships between mining management and miners. The majority of respondents supported a move away from company-based wage negotiations to a collective process at industry level. Uncertainty on the role of the Chamber of Mines (COM) as a result of trust issues also emerged. There were mixed responses as to whether union rivalry played any role in the breaking of trust between management and miners and between miners themselves. 4 Respondents representing mining companies believed in the role played by union rivalry. Some respondents representing mining companies were of the view that the doctrine of shareholder sovereignty and primacy be placed on a financially, humanely and politically sustainable foundation to ensure the long-term optimal profitability of the platinum mining industry in South Africa. These respondents believed that if employees accepted that profits were required for the sustainability of the companies, they would be committed to productivity improvements.
MBA
Keywords: Platinum mines and mining -- South Africa -- Management. Social responsibility of business -- South Africa. Corporate governance -- South Africa.